TEMPERATURE ZONING OF IRAQ FOR ASPHALT MIX DESIGN - Saadi Abbas, Alaa (Journal of Engineering and Sustainable Development, 2017)
Currently, asphalt grading in Iraq depends on two types; penetration grade and viscosity grade. These grades did not give an impression on asphalt pavement performance because it is dependent on fixed temperature tests. In this paper, the Iraq map was developed by using the Superpave method to find performance grades. High and low pavement temperature was calculated. Contour maps for high and low pavement temperatures are developed by using a geographic information system (GIS). A map presented the temperature zones in Iraq in terms of asphalt performance grade. The data on temperature was taken from 48 weather stations distributed in all regions of Iraq. It has been found PG70-10 and PG76-10 cover more than 70% of the parts of Iraq.